Husserl e os limites da redução fenomenológica nas idéias I - Simão, Jean Leison (2009)
Lack of understanding of the Husserlian phenomenological issues peculiarity in relation to science fact and in particular the psychology (either a lack of understanding come from philosophers or psychologists outside or not the phenomenological movement) constitutes the rationale for developing this work. If even some of his disciples did not comprehend it, It would not be enough to assume that today (i.e. the distance of a century) these problems remain misunderstood. Thus, our specific goal is to understand the scope and limits of the phenomenological reduction, the method that give us free access to the terrain phenomenological. So we can effectively overcome the obstacles that keep the spiritual thought locked in his own horizon. Our investigations are focused on the first two parts of Ideas I, the first work that came public with the specific goal to be a systematic introduction to phenomenology. In the first chapter of this work, we keep proper within the formal logic, we will investigate the differences of principle between essences and facts, as well as between science and science of essences of facts in order to understand how philosophy should it be a science of essences, peculiar and autonomous. In the second and third chapter, however, we will move it in phenomenological terrain. While the second will investigate the designation and the effective of restriction on the natural positing to finally understand how such a reduction takes place; In the third, the goal is to establish a definite distinction between "abstraction" in the phenomenological positing of mere abstractions of the natural sciences. From the primary exclusion (a term that allude to manifestation of the reduction) it will be develop other attempts of exclusion, thus extending the phenomenological reduction to other transcendent spheres of being. With these weights we expect to have finally got rid of that constant temptation to establish a erroneous metabasis own thought that closes a natural theoretical positing.